Parturiliikkeen näyteikkuna, Liisankatu 14 - Peltonen, Jarno
sisällön kuvaus: Parturiliikkeen näyteikkuna, Liisankatu 14.
Keywords: mainokset; asuinrakennukset; mainonta; parturit; Suomi, Uusimaa, Helsinki, Kruununhaka Helsinki, Liisankatu 14